2019
DOI: 10.1002/elps.201800491
|View full text |Cite
|
Sign up to set email alerts
|

Slippage mutation rates in 15 autosomal short tandem repeat loci for forensic purposes in a Southeastern Brazilian population

Abstract: Slippage mutation rates in 15 autosomal short tandem repeat loci for forensic purposes in a Southeastern Brazilian populationWell-defined estimates of mutation rates in highly polymorphic tetranucleotide STR loci are a prerequisite for human identification in genetics laboratory routines useful for civil and criminal investigations. Studying 15 autosomal STR loci of forensic interest (CSF1PO, D2S1338, D3S1358, D5S818, D7S820, D8S1179, D13S317, D16S539, D18S51, D19S433, D21S11, FGA, TH01, TPOX, and vWA), we det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Since the father from the Case 1 was 65 years old at the birth of child, we assume that his age could be the cause of mutations occured in both autosomal and X-linked STRs. Considering all aforementioned, knowledge about mutation rates and possible mutational processes of different STR loci is important for accurate genetic profiles interpretation (Qian et al, 2015;Hamester et al, 2019). As previously mentioned in the Introduction section, a number of population-genetic studies, focused on evaluating of forensic efficiency parameters of STR markers (Grskovic et al, 2013 2016; Crnjac et al, 2017;Veselinovic et al, 2018;Al-Eitan et al, 2019;Al-Eitan et al, 2020;Pilav et al, 2020;Takic Miladinov et al, 2020) indicated a high degree of reliability of these markers important for all kinds of forensic-genetic analyses, including kinship and parentage testing.…”
Section: Discussionmentioning
confidence: 99%
“…Since the father from the Case 1 was 65 years old at the birth of child, we assume that his age could be the cause of mutations occured in both autosomal and X-linked STRs. Considering all aforementioned, knowledge about mutation rates and possible mutational processes of different STR loci is important for accurate genetic profiles interpretation (Qian et al, 2015;Hamester et al, 2019). As previously mentioned in the Introduction section, a number of population-genetic studies, focused on evaluating of forensic efficiency parameters of STR markers (Grskovic et al, 2013 2016; Crnjac et al, 2017;Veselinovic et al, 2018;Al-Eitan et al, 2019;Al-Eitan et al, 2020;Pilav et al, 2020;Takic Miladinov et al, 2020) indicated a high degree of reliability of these markers important for all kinds of forensic-genetic analyses, including kinship and parentage testing.…”
Section: Discussionmentioning
confidence: 99%
“…Since the father from the Case 1 was 65 years old at the birth of child, we assume that his age could be the cause of mutations occured in both autosomal and X-linked STRs. Considering all aforementioned, knowledge about mutation rates and possible mutational processes of different STR loci is important for accurate genetic profiles interpretation (Qian et al, 2015;Hamester et al, 2019). As previously mentioned in the Introduction section, a number of population-genetic studies, focused on evaluating of forensic efficiency parameters of STR markers (Grskovic et al, 2013 2016; Crnjac et al, 2017;Veselinovic et al, 2018;Al-Eitan et al, 2019;Al-Eitan et al, 2020;Pilav et al, 2020;Takic Miladinov et al, 2020) indicated a high degree of reliability of these markers important for all kinds of forensic-genetic analyses, including kinship and parentage testing.…”
Section: Discussionmentioning
confidence: 99%